ST elevation myocardial infarction in a healthy teenager with no risk factors - Sheikh, Wasil Rasool; Verma, Ankur; Haldar, Meghna; Jaiswal, Sanjay (Indian Journal of Case Reports, 2016)
Myocardial infarction is not common in patients younger than 45 years. Young patients can experience a myocardial infarction in the presence or absence of atherosclerosis. We report a case of an 18-year-old male patient who presented with chest pain in the emergency department. There were neither any risk factors of coronary artery disease nor any co-morbidity. Investigations revealed an acute myocardial infarction with ST-segment elevation in ECG. On coronary angiography, mid 90% thrombus was seen in the left anterior descending artery, the cause of which remains unknown. Although rare, acute myocardial infarction should be considered in young adults or teenagers presenting with chest pain. Also, it can affect teenagers in the absence of traditional coronary risk factors or co-morbidities.